14-3-3β Is necessary in the regulation of polarization and directional migration of alveolar myofibroblasts by lipopolysaccharide. (7th February 2020) - Li, Jianhui; Gong, Xiaohui
Abstract: Aims: Bronchopulmonary dysplasia (BPD) is characterized by alveolarization arrest. During alveolarization, alveolar myofibroblasts are thought to migrate into the septal tips and elongate secondary septa. Lipopolysaccharide (LPS) exposure has been reported to disrupt directional migration and final location of alveolar myofibroblasts in a rat model of BPD induced by intra-amniotic injection of LPS. However, molecular mechanisms that control directional migration of alveolar myofibroblasts have not so far been investigated clearly. Materials and Methods: We assessed the polarization of myofibroblast using scrape wounding assays combined with Golgi tracking. Transwell migration assay was used to detect the directional migration of myofibroblasts. Pull-down assays were performed to isolate the active GTP-bound form using the RhoA activation assay kits. Western blotting analysis was performed to evaluate the changes in protein expression. Functional analysis was performed via siRNA interference. Results: Here, we showed that LPS might affect the directional migration of myofibroblasts by disturbing the polarization of myofibroblasts. In addition, as a main member of RhoGTPases family which plays a vital role in establishing and maintaining cell polarity, RhoA activity was significantly upregulated in myofibroblasts treated with LPS, while activity of epidermal growth factor receptor (EGFR) was upregulated and overexpression of its ligand, TGF-α, in myofibroblasts by LPS treatment. AG1478, an EGFR inhibitor, could abrogate the upregulated RhoA activity of myofibroblasts by LPS and rhTGF-α. Moreover, if we knock down 14-3-3β, LPS and rhTGF-α could not activate RhoA and disturb myofibroblasts polarization. Conclusions: Taken together, our findings suggest that LPS exposure may increase RhoA activity of myofibroblasts by TGF-α/EGFR/14-3-3β signaling pathway, and then disturb myofibroblasts polarization and directional migration.